Theoanthropocentric: Learning Strategies for Improving Students’ Conceptual Understanding - Muhammad Darwis Dasopang (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2020)
Learning objectives can be achieved in various ways, one of which is by implementing learning strategies. This study aims to explore the effectiveness of Theoanthropocentric learning strategies for improving students’ conceptual understanding skills. The research population is all junior high school students (SMP), and the sample comprises students from class VIII. The random cluster sampling technique was used to choose the study’s sample. The data collection method used in this research is the conceptual understanding test. Descriptive and inferential statistics serve for data analysis, including the independent t-test. The results show a significant difference between the conceptual understanding of students who used Theoanthropocentric learning strategies and those who did not use Theoanthropocentric learning strategies. The descriptive statistical test results show that the students in the experimental group have a higher mean score than students in the control group. The independent t-test result has strengthened the statistical test results, namely, 0.00 (p 0.05), from the finding, it follows that the application of theoanthropocentric learning strategies has an enormous impact on improving students’ conceptual understanding skills. Therefore, the Theoanthropocentric approach could be used as a solution to improve students’ conceptual understanding skills.